On the existence of zero-group velocity modes in free rails: Modeling and experiments. (December 2022) - Wu, Yuning; Cui, Ranting; Zhang, Keping; Zhu, Xuan; Popovics, John S.
Abstract: Zero-group velocity (ZGV) modes in rails are studied through simulation and experiments in this work. Local resonances associated with ZGV modes appear as distinct, sharp peaks in the frequency amplitude spectrum, whose resonant frequencies can serve as indicators of the local structural integrity condition of the rail itself, assuming that one can excite, detect, and identify wave mode type with confidence. To better understand these interesting modes, semi-analytical finite element (SAFE) analysis is implemented to compute dispersion curves of a standard rail and to identify potential ZGV points. A fully discretized Finite Element (FDFE) model then simulates responses of a free rail when subjected to impulse-based dynamic testing. Experimental impulse vibration data are collected from a 25-m rail with multiple impact-receiver configurations to understand the detectability and excitability of specific resonances associated with ZGV modes in rails. Spatial sampling of wave disturbance is performed to calculate the dispersion relations experimentally via two-dimensional Fourier Transforms (2D-FFT). The excellent agreement between simulation and experimental results confirms the existence of ZGV modes and cutoff frequency resonances in rails and verifies the feasibility of using impulse-based dynamic tests for the promotion of ZGV modes.